2009
DOI: 10.1111/j.1745-4522.2009.01148.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF ZERO‐TRANS INTERESTERIFIED AND NON‐INTERESTERIFIED SHORTENINGS AND BREWER'S SPENT GRAIN ON COOKIE QUALITY

Abstract: The effects of non‐interesterified (non‐in‐es) and chemically interesterified (in‐es) cottonseed oil (CO), palm oil (PO) and CO : PO blend (1:1, weight basis) and brewer's spent grain (BSG) on quality of cookies were studied. Incorporation of non‐in‐es and in‐es CO and CO : PO blend improved the nutritional value of the cookies by altering the fatty acid composition. The experimental shortenings had zero‐trans fatty acids (TFA) and considerably higher linoleic acid contents than hydrogenated shortening (HS). i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The results indicated that interesterification can be successfully applied in cake shortening production, resulting in decrease in the consumption of TFA (Dogan et al ., 2007). Also, in a study by Ozturk et al . (2009) the IE experimental shortenings had zero‐TFA and considerably higher linoleic acid contents than HS.…”
Section: Introductionmentioning
confidence: 85%
“…The results indicated that interesterification can be successfully applied in cake shortening production, resulting in decrease in the consumption of TFA (Dogan et al ., 2007). Also, in a study by Ozturk et al . (2009) the IE experimental shortenings had zero‐TFA and considerably higher linoleic acid contents than HS.…”
Section: Introductionmentioning
confidence: 85%
“…Chemical and enzymatic interesterification modify the physical properties of oils by rearranging the distribution of fatty acids on the glycerol backbone without changing their chemical composition (Norizzah et al 2004). Recently, interesterification has been applied to improve the cold spreadability of butterfat-canola oil blends (Rousseau and Marangoni 1999), and the production of margarine (Alpaslan and Karaali 1998), frankfurter (Vural and Javidipour 2002;Vural et al 2004), Turkish-type salami (Javidipour and Vural 2002;Javidipour et al 2005) cheese (Javidipour and Tunçtürk 2007), cake (Dogan et al 2007) and cookie (Öztürk et al 2008;Ozturk et al 2009;Dinç et al 2011). However, interesterification can be successfully applied in different food products, there are a few reports related to the effects of interesterification on oxidative stability of fats and oils.…”
Section: Introductionmentioning
confidence: 99%